Dude, Where's My Gun? A near-surface geophysics case-study. Issue 1 (1st December 2019) - Dean, Tim; Costall, Alex; Sik, Nichole; Blylevens, John; Pethick, Andrew; Howman, Dominic
Summary: Buckland Hill, near Fremantle in Western Australia, was the site of a costal defence battery from 1942 until 1963. After the army left the site in the mid-1980s, it was developed for housing, but the battery area was retained as a park and later developed into a military museum. The battery included three 5.25-inch guns of which only one is currently visible, the other two having been either demolished or buried. To identify the location of the two remaining positions we acquired ground penetrating radar, 3D electrical resistivity imaging, 2D seismic, frequency domain electromagnetic and magnetic data. All the methods were successful to some extent, but Frequency domain EM was the most useful. From our results we are confident that the second gun position has survived largely intact and discussions are now underway to excavate it. Despite difficulty in accessing the suspected position of the third emplacement, there is no indication that it still exists (it was probably demolished when the area was developed for housing).